Assessment of anaesthesiologist and public hospital preparedness for the prevention and treatment of local anaesthetic systemic toxicity (LAST): a national survey - Alif Noikham; Tatcha Tratornpisuttikul; Pawinee Pangthipampai (Annals of Medicine)
Background Local anaesthetic systemic toxicity (LAST) is a significant risk associated with the use of local anaesthetics. Despite existing prevention and management guidelines, the increasing use of local anaesthetics raises concerns about LAST. This study aims to assess the preparedness of anaesthesiologists and hospitals to manage LAST, following the Third American Society of Regional Anesthesia and Pain Medicine Practice Advisory.Methods The research questionnaire is developed and validated. The questionnaire focuses on a three-dimensional framework for anaesthesiologist preparedness: prevention, diagnosis and treatment. Furthermore, the questionnaire also assesses hospital preparedness based on the availability of resources to manage LAST. The study includes anaesthesiologists from public hospitals in Thailand. Data are collected by mailing letters to all public hospitals.Results The survey collected responses from 284 anaesthesiologists in 108 hospitals, reflecting a response rate of 57.8%. Anaesthesiologists consistently applied LAST prevention methods at an average rate of 85.8%. They recognized 12 of 16 LAST symptoms. Regarding LAST treatment, 97.1% of them correctly identified the required drug. Based on prespecified criteria, 77.5% of anaesthesiologists were considered prepared in all dimensions. Lipid emulsion and cognitive aids were available in 69.4% and 42.0% of the hospitals, respectively. Hospitals that performed 6–20 regional blocks per day were significantly associated with higher preparedness for LAST.Conclusions Anaesthesiologists in this study are generally well prepared for managing LAST, but there are areas that require improvement, particularly in hospital resources, such as the availability of lipid emulsion and cognitive aids, as well as the retrieval process for lipid emulsion.